(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Clinical, staff Satisfaction Survey was a study with the purpose ofacquiring feedback from the Employees. Because this was the first time for thissurvey, various distribution methods were tested to determine which would bethe most effective and obtain the highest response rate. Overall, there was ahigh level of satisfaction with the skills and knowledge taught to the staff.Most of the employees surveyed indicated that they were enthusiastic, listenedto understand and learn, had the ability to work well in groups, couldunderstand and speak the language of their business, and had the ability tolearn new skills and knowledge on the job.